The moderating effect of audit quality on the relation between shareholder activism and earnings management: Evidence from France - Francis Kwaw Andoh; Nehemiah E. Osoro; Eliab Luvanda (Contemporary Economics, 2019)
The present paper aims to provide empirical evidence regarding the impact of shareholder activism on earnings management. Specifically, it is focused on investigating the moderating role of an external governance mechanism such as external audit quality. Based on a sample of French companies listed on the French stock market index (SBF 120 index) from 2008 to 2012, we apply several multiple regressions using a standard methodology devised by Aiken and West (1991). We find that external audit quality plays a moderating role between shareholder activism and earnings management in such a way that it greatly helps to attenuate the relationship in the presence of high-quality external audits.
Keywords: M41; M42; M48; 330; shareholder activism; discretionary accruals; earnings management; audit quality index